Ensuring the competitiveness of business structure based on the strategy of development in modern conditions (Путеводитель предпринимателя, 2020)
The present article is devoted to analysis ofthe competitiveness ofbusiness structure based on a development strategy. This article gives us the definition ofcompetitiveness and in this article the author examines the levels ofcompetitiveness ofbusiness structure, key problems ofbusiness structures. It is indicated that the level ofdomestic business activity in the field of non-technological innovations is rather low that is the reason oflow competitiveness of domestic enterprises in comparison with foreign countries. The definition of development strategy is given. It is indicated that improvement of competitive positions and increase of competitiveness must be one ofthe objectives of development strategy. There are examined the strategies of competitiveness based on different competitive advantages as well as their disadvantages including the fact that in accordance with the developed classifications the companies by their economic nature are strictly competitive and not targeted on cooperation. However the global hypercompetition generates the idea of uniting the efforts of business structures on joint market penetration.